To Live For A Future - Craig, Anita P (PINS-Psychology in Society, 2026)
In this article I want to outline a number of characteristics which together configure a certain style to our times. This is meant to draw us into a more deliberate assessment of where we are heading, given the way we think and live nowadays. Central to the article is a belief that we in this young republic with its long (indigenous) and relatively short (colonial) history need discourses marked by reasonableness and organised future directedness. Moreover, I am of the opinion that this is not often and widely enough the case in South Africa I thus want to highlight some of the ways we talk and live which I believe to be antithetical to living for a future which will serve us all well. I also want to assume that we are committed to living well and to harnessing the best possible future for ourselves through present beliefs and projects, moreover, that we generally believe, more or less, that to live well means to live reasonably - admitting of course a very long history of changing ideas about what "reason" and "reasonably" mean I will briefly describe, below, two conceptions of reasonableness, one by Alfred North Whitehead and one by Stephen Toulmin, both which I find particularly attractive.